Enhancing the Learning Activities of First-Grade Elementary Students through the Drill and Practice Method in the Topic of Object Length Comparison - Mega Saraswati; Nur Kholis (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study investigates the effectiveness of the drill and practice method in enhancing the learning activities of first-grade elementary students on the topic of object length comparison. Implemented at SD Negeri Kedunggebang, Banyuwangi Regency, the research employed a qualitative descriptive approach involving 26 students and their homeroom teacher. Data were collected through observations, interviews, and documentation to capture students’ engagement, comprehension, and accuracy in using measurement tools. The results indicate that repetitive and structured practice significantly improved students’ understanding and performance in measuring and comparing object lengths. The method not only enhanced students' accuracy in using rulers but also increased their enthusiasm for learning. Group division and contextual practice further supported student learning outcomes. Despite challenges related to students’ early cognitive development and learning motivation, the drill and practice method proved to be an effective instructional strategy for developing foundational mathematics skills, particularly in measurement.